(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
This article provides a comprehensive overview of one of the global issues – environmental problems – and discusses the United Nations Development Programme aimed at addressing these issues. It also highlights how this system helps coordinate efforts to protect nature.